Sibling Additions, Resource Dilution, and Cognitive Development During Early Childhood. Issue 2 (15th September 2016) - Workman, Joseph
Abstract: A sizable literature found an inverse association between number of siblings and developmental outcomes. Little is known about this relationship during the earliest years of children's lives, a period when parental attention and resources matter greatly for cognitive development. Using the Early Childhood Longitudinal Study–Birth Cohort, a nationally representative sample of American children born in 2001, this study investigates the inter‐relationships between siblings, home resources, and cognitive development during the years before formal schooling. To address unobserved differences between families, child fixed effects models were used to assess children's experiences before and after the birth of a sibling. The birth of a sibling was not significantly associated with lower cognitive development, even when the age spacing between the siblings was small. Concerning home resources, interpersonal resources mattered a great deal for young children's cognitive development, but interpersonal resources were not shaped by the presence of siblings.